Input production joint venture - Gianpaolo Rossini; Cecilia Vergari (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2009)
In many industries it is quite common to observe firms delegating the production of essential inputs to independent ventures jointly established with competing rivals. The diffusion of this arrangement and the favourable stance of competition authorities call for the assessment of the social and private desirability of Input Production Joint Ventures (IPJV), which represent a form of input production cooperation, not investigated so far. IPJV can be seen as an intermediate organizational setting lying between the two extremes of vertical integration and vertical separation. Our investigation is based on an oligopoly model with horizontally differentiated goods. We characterize the conditions under which IPJV is privately optimal finding that firms' incentives may be welfare detrimental. We also provide a rationale for the empirical relevance of IPJV both in terms of its ability to survive and in terms of disengagement incentives.
Keywords: 330